Combined Solar Chimney Power Plant and Solar Still - Hammadi, Salman H. (Basrah Journal for Engineering Sciences, 2016)
This study presents solar chimney power plant integrated with sea water desalination system. A simple mathematical model is based on the conservation of mass and energy. The results show that the integrated system of solar chimney power plant and solar still can achieve simultaneously. The analysis is performed for both summer and winter at latitude 30 o N. It’s noted that, the water layer thickness is of a significant effect on the fresh water productivity while the dimensions of solar chimney and the solar collector are of a minor effect. The productivity of fresh water and output power for summer are the highest. The present work is compared with experimental data of the other work and showed a good agreement.